AN ANALYSIS ON THE EFFECTS OF CORONAVIRUS (COVID-19) ON THE FINANCIAL MANAGEMENT OF MULTINATIONAL CORPORATIONS - Zayed, Nurul Mohammad; Islam, K. M. Anwarul; Shahi, Shahiduzzaman Khan; Rahman, Md. Sazidur; Raisa, Tahsin Sharmila (Australian Finance & Banking Review, 2021)
This paper develops a sensible framework to get a handle on the spatiotemporal plans of the COVID-19 event, its real nature, and its implications to the Financial Management of MNCs (Multinational Corporations). In the most straightforward structure, the construction of multinational Corporations is included a parent organization that holds all licensed innovation rights, contract makers or undeniable makers which complete the creative work in the nations with low work costs, and the restricted or undeniable wholesalers that sell the completed merchandise in different business sectors and behaviors market explores in their nations of activity. The pandemic effect on financial movement contrasts as far as extent and force. This has delivered unrivaled proportions of shortcomings. This paper tries to diagram the overall elements of worldwide Financial Management of MNCs (Multinational Corporations) with country explicit dangers and primary dangers. Fundamental data is accumulated from different online media, adroit journals, various kinds of examination papers, and other online sources, etc. The globalization of Financial Management of MNCs (Multinational Corporations) is coordinated to the enormous extension of greatness and enhancement of monetary exchanges. At long last, all areas show and portray in detail this subject and give a few suggestions to conquer the present circumstance. JEL Classification Codes: F36, G32, F23.